Flexibilidade entre plantio e arrendamento rural no Brasil - Marcelo Guedes Pecly; Rafael Igrejas (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
Brazil is the world's largest producer of sugarcane, product with history and importance in the Brazilian agribusiness. The State of S\~ao Paulo is responsible for 50% of Brazilian production. Harvested area is estimated at 4.25 million hectares. The metropolitan region of Ribeir\~ao Preto, in S\~ao Paulo, is the largest sugarcane producer in the country, accounting for 25% of S\~ao Paulo production. In the domestic market, the profitability of sugarcane production at the mills, as well as the market price, are impacted not only by production costs, but also by the costs of land leasing to local owners. The landowners of sugarcane farms have the flexibility of sugarcane production, or to lease the area to the mills. In scenarios of high costs and low productivity, such as 2018/2019 harvest, there was an increase in contract lease cancellation by the mills. In the previous harvests (2016/2017), the increased demand for lease contract was correlated to an increase in land productivity and more competitive lease prices. The flexibility between production and leasing in rural properties is well known by the sector's agents, but it needs to be appropriate addressed using decision analysis methods. This type of decision under uncertainty can be properly conducted by Real Options Theory. Thus, in this study, is proposed a model to evaluate the managerial decision of sugarcane production by the landowners, using the land was previously leased to the mills. In the model, the sugarcane price in the domestic market of Brazil (açúcar total recuperável - ATR) is considered the main uncertainty of the project. The model was applied to the valuation of a rural property in Ribeir\~ao Preto, in the state of S\~ao Paulo. The results show that the option to start the sugarcane production once the land was previously leased, adds 5.17% to the future cash flow of the landowner in present value, which represents an increase of US 1.7/t. The main contribution of the study is the decision model, which allows evaluating the impact of managerial flexibility of landowners on agribusiness in Brazil. The landowners using real options approach for decision making, can optimize their resources.
Keywords: G13; Q12; R14; 330; flexibility; Real Options; sugarcane production; land leasing; agricultural economy